Persepsi Siswa terhadap Public Speaking Mahasiswa PPL UIN Mataram dalam Membangun Pemahaman Siswa di MA Plus Nurul Islam Sekarbela - Fitra Salami; Dedi Riyan Rizaldi; Muhammad Fahrurrozi; Evina Apriyani; Nilwan; Ziadatul Fatimah (Lembaga Einstein College (LEC), 2024)
The purpose of this study was to describe students' perceptions of the public speaking abilities of UIN Mataram PPL students, with the aim of building understanding among MA Plus Nurul Islam Sekarbela students. This study uses a qualitative approach with a descriptive case study research type. The subjects used in this study were UIN Mataram PPL students and class XI MA Plus Nurul Islam Sekarbela students. Research data related to students' public speaking abilities and student understanding were obtained through observation techniques and questionnaire techniques. Research data were analyzed by applying qualitative data analysis consisting of data reduction, data display, and verification. Based on the study, students' perceptions of public speaking of UIN Mataram PPL students in class XI were classified as positive with a very good category range and could build understanding of class XI students in studying the material taught in class with a very good category range